Firms, governments, and climate policy incentive-based policies for long-term climate change - Carraro, Carlo; Egenhofer, Christian, 1960-; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : E. Elgar, 2003)
This book analyses the policy mixes that provide the best possible incentives for firms and governments to act on climate change and sign up to international climate agreements. In doing so, the authors address a multitude of related issues including the linkages between flexible mechanisms and voluntary agreements; regulation and taxation; the opportunities and barriers of the Kyoto Protocol for industry; and the incentives for firms to undertake climate-related R&D and investments. As well as illustrating the environmental benefits and cost-effectiveness of alternative policy mixes in reducing GHG emissions, the authors also offer sensible policy prescriptions for increasing the numbers of countries that ratify and implement climate agreements.
1. The compatibility of the Kyoto mechanisms with traditional environmental instruments -- 2. Negotiated agreements and climate change mitigation -- 3. Kyoto flexible mechanisms : opportunities and barriers for industry and financial institutions -- 4. Traditional environmental instruments, Kyoto mechanisms and the role of technical change -- 5. The future evolution of the Kyoto protocol : costs, benefits and incentives to ratification and new international regimes.
Includes bibliographical references and index.
Keywords: Environmental policy; Climatic changes -- Government policy; Age distribution (Demography) -- Environmental aspects; Sustainable development; Energy consumption -- Environmental aspects; Electronic books